Impact of the five-pattern personality traits of traditional Chinese medicine on workplace violence and depression among nurses - ZhiHui Gu; ChenXin Yang; MengYao Li (BMC Nursing, 2025)
Abstract Background Depression seriously damage the health of nurses. It is not conducive to the provision of medical services and hospital management. Meanwhile, nurses are a highly vulnerable group to workplace violence (WPV), increasing the risk of depression. Nurses with different personalities may have various views and feelings towards WPV, and their impact on depression may also vary. This study aims to reveal the impact of the five-pattern personality traits of traditional Chinese medicine (TCM) on WPV and depression among nurses, providing a new perspective for managers to implement psychological interventions. Methods A cross-sectional study was conducted. 2,788 valid questionnaires nationwide were collected based on Wenjuanxing from June to July 2024. We used Patient Health Questionnaire Depression Scale-9 item, The five- pattern Personality Traits of TCM Scale, and Workplace Violence Scale. We used latent class analysis, structural equation modeling, and simple slope analysis to analyze depression classes, mediating effects, and moderation effects, respectively. Results Depression is classified into three types: “Good mental health group” (34.2%), “Moderate depression group” (23.0%), and “Severe depression group” (42.8%). “Taiyang”, “Shaoyang”, and “Balance of Yin-Yang” personalities alleviate nurses’ feelings of WPV, thereby reducing the impact of WPV on depression. The values of mediating effect are -0.402, -0.393, and -0.426, respectively (P < 0.05). “Taiyin” personality exacerbate nurses’ perception of WPV, thereby increasing the impact of WPV on depression. The value of mediating effect is 0.418 (P < 0.05). “Taiyang” and “Shaoyang” personalities reduce the impact of WPV on depression of nurses, and the effect become more significant as the scores increase. The values of moderating effect are 0.033 and -0.0563 respectively (P < 0.05). “Taiyin” and “Shaoyin” personalities increase the impact of WPV on depression, and the effect become more significant as the scores increase. The values of moderating effect are -0.0444 and -0.0220 respectively (P < 0.05). Conclusions The prevalence of depression and WPV among Chinese nurses is serious. Excellent personality effectively improve the relationship between WPV and depression. Nursing managers should arrange suitable positions for nurses based on their different personality traits. At the same time, it is necessary to actively cultivate excellent personality traits in nurses to reduce the frequency of WPV and improve their mental health.